2015
DOI: 10.22452/mjs.vol34no2.3
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Amino Acid Compositions of the Pond-Cultured Spotted Barb, Puntius Binotatus

Abstract: The pond culture of spotted barb (Puntius binotatus) has been started in Sabah. However, the nutritional values of these cultured P. binotatus as a protein source for human consumption have never been assessed. Therefore, the proximate and amino acid compositions of these cultured P. binotatus (n = 6, 3 females and 3 males) were evaluated to provide baseline information on its nutritional quality. The fish whole body contained about 18% and 9% of crude protein and lipid, respectively (in wet weight basis), 11%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 6 publications
0
10
0
9
Order By: Relevance
“…The formula were logarithm-transformed to ln W= ln a + bln L, then the linear regression graph was plotted using MS-Excel computer program to estimate the values of the constant (a), slope (b), the correlation coefficient (r) (and its significant level) of the LWRs. The growth condition of the fish was then categorized using the b values; when b = 3, the fish has attained isometric growth, b < 3 indicated negative allometric, and b > 3 indicated positive allometric growth (Lim et al 2013).…”
Section: Calculations Of Lwr and Rcfmentioning
confidence: 99%
See 2 more Smart Citations
“…The formula were logarithm-transformed to ln W= ln a + bln L, then the linear regression graph was plotted using MS-Excel computer program to estimate the values of the constant (a), slope (b), the correlation coefficient (r) (and its significant level) of the LWRs. The growth condition of the fish was then categorized using the b values; when b = 3, the fish has attained isometric growth, b < 3 indicated negative allometric, and b > 3 indicated positive allometric growth (Lim et al 2013).…”
Section: Calculations Of Lwr and Rcfmentioning
confidence: 99%
“…The RCF calculation was performed by using formula Kn = W/ W' where W is the observed weight, and W' is the expected weight of individual fish (a L b ) with the earlier estimated b value (Fafuiye and Oluajo, 2005;Farzana and Saira, 2008;Lim et al, 2013). If Kn = 1 or more, this outcome indicated that the fish has achieved the expected growth, and vice versa.…”
Section: Calculations Of Lwr and Rcfmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish inhabit in a tropical climate and commonly prefer the freshwater with a temperature range of 24-26 o C and a 6.0-6.5 pH (Kottelat, 2013). In addition, the fish species has high protein containing lysine (23.5 mg/g sample) which considered as an essential amino acid (Lim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Analisis hubungan panjang bobot ikan digunakan untuk menentukan faktor kondisi yang mengacu pada tingkat kemontokan ikan (Fafuiye & Oluajo 2005), dan kesesuaian dengan lingkungan (Farzana & Saira 2008). Hubungan panjang bobot merupakan metode yang umum diterapkan di perikanan untuk penilaian stok (Hossain et al 2012), survei dampak lingkungan, dan mengevaluasi kondisi ikan yang dipelihara di lingkungan budi daya (Olurin & Aderibigbe 2006, Kumar et al 2013, Lim et al 2013. Hubungan panjang bobot dan faktor kondisi relatif (FK) juga dapat digunakan untuk membandingkan kondisi ikan pada lokasi yang berbeda (Isa et al 2010, Zakeyudin et al 2012, Gerami et al 2013.…”
unclassified